Spinal injuries - Suero Castro, Carlos (Cirugía del Uruguay, 1974)
The skeleton is involved in neck wounds in cases of grave politraumatized patients or in bullet wounds,'!'he latter produce fractures of varying seriousness, but rarely luxo-fractures. Deferred spine wounds are nearly always due to inopportune mobilization. The author revises clinical elements which permit diagnosis of spinal lesions in patients with neck wounds and lists types of lesions that render dangerous hyperextension of neck, prior to intubations and surgical exploration. The various procedures for fixing lesioned spine during intra and post-operatory periods, are described.